PHYSICAL-CHEMICAL CHARACTERIZATION OF RAW MILK IN DAIRY INDUSTRIES AND STORAGE CENTERS LOCATED IN THE PROVINCE OF CHIMBORAZO- ECUADOR - Miler Gabriel Duchi Yaguachi, Miler Gabriel Duchi Yaguachi; Guerrero Luzuriaga, Sebastián Alberto; Rojas Vallejo, María Fernanda; Jaramillo Bayas, Ramiro Germán (Tierra Infinita, 2023)
Milk is considered a food of high nutritional value, necessary for food and nutrition. Milk production in Ecuador is one of the most important livestock activities in terms of the country’s economy. For this reason, it is necessary to control milk from milking to marketing. The parameters to determine the quality of milk prior to industrialization are evaluated through physical, chemical and microbiological analyses. The purpose of this research was the physicochemical characterization of raw milk from dairy industries and collection centers located in the Province of Chimborazo. To carry out the physical-chemical analysis, milk samples were collected from each supplier, determining quality parameters established by the INEN 9 Standard, such as temperature, density, percentage of fat, protein and total solids. This sampling was carried out with the purpose of identifying compliance and non-compliance with these parameters in the different collection centers and dairy industries, evidencing a 4% non-compliance with these quality parameters; In order to improve milk quality, it is proposed to implement consecutive controls at these establishments, in addition to promoting good milking practice programs. In this study, a labeling was carried out where 90% of the dairy industries and collection centers are labeled green, which indicates that they maintain adequate compliance with the quality parameters, 8%, however, are labeled yellow and the 2% are found in red labeling